The Role of the Principal in Carrying Out Supervision to Improve Teacher’s Competence - Herlina, Herlina; Arafat, Yasir; Mahasir, Mahasir (Yayasan Sembilan Pemuda Indonesia, 2023)
The purpose of this research is (1) to find out the role of the principal as a supervisor in helping teachers lead classes in improving teacher competence at SD Negeri 24 Talang Kelapa, (2) to find out the role of the principal as a supervisor in helping teachers plan learning programs in improving teacher competence at SD Negeri 24 Talang Kelapa and (3) to find out the role of the principal as a supervisor in helping teachers carry out the learning process in increasing teacher competence at SD Negeri 24 Talang Kelapa. The method used in this research is descriptive qualitative method with in-depth interviews. The results of this study found that (1) the role of the principal in supervising the teacher's ability to lead a class, starting with supervising the planning of lesson plans, implementing learning in class and evaluating learning, (2) the supervisory role of the school principal in increasing teacher competence is demonstrated by providing guidance, identifying teacher deficiencies and planning the training needed by teachers and (3) the role of the school principal as a supervisor in helping teachers carry out the learning process in improving teacher competence at SD Negeri 24 Talang Kelapa is carried out by providing support to teachers with training and then evaluating how the results are, encouraging teachers to attend trainings and workshops both during online and offline.